2018
DOI: 10.1002/sim.7854
|View full text |Cite
|
Sign up to set email alerts
|

A validation sampling approach for consistent estimation of adverse drug reaction risk with misclassified right‐censored survival data

Abstract: Patient electronic health records, viewed as continuous-time right-censored survival data, can be used to estimate adverse drug reaction risk. Temporal outcome misclassification may occur as a result of errors in follow-up. These errors can be due to a failure to observe the incidence time of the adverse event of interest (due to misdiagnosis or nonreporting, etc) or an actual misdiagnosis of a competing adverse event. As the misclassifying event is often unobservable in the original data, we apply an internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Covariate measurement error, particularly classical measurement error or extensions of it, has been well studied in the literature, and methods to correct the bias resulting from such error have been well developed (Carroll et al., 2006). Although less attention has been given to errors in an outcome of interest, there has been some recent work looking at errors in binary outcomes (Magder & Hughes, 1997; Edwards et al., 2013; Wang et al., 2016), discrete time‐to‐event outcomes (Hunsberger et al., 2010; Magaret, 2008; Meier et al., 2003), and to a lesser extent, continuous time‐to‐event outcomes (Gravel et al., 2018; Oh et al., 2018). There has been even less work to understand the impact of errors in both covariates and a time‐to‐event outcome, but it has recently been shown that ignoring such errors can cause severe bias in estimates of effects of interest (Boe et al., 2020; Giganti et al., 2020; Oh et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Covariate measurement error, particularly classical measurement error or extensions of it, has been well studied in the literature, and methods to correct the bias resulting from such error have been well developed (Carroll et al., 2006). Although less attention has been given to errors in an outcome of interest, there has been some recent work looking at errors in binary outcomes (Magder & Hughes, 1997; Edwards et al., 2013; Wang et al., 2016), discrete time‐to‐event outcomes (Hunsberger et al., 2010; Magaret, 2008; Meier et al., 2003), and to a lesser extent, continuous time‐to‐event outcomes (Gravel et al., 2018; Oh et al., 2018). There has been even less work to understand the impact of errors in both covariates and a time‐to‐event outcome, but it has recently been shown that ignoring such errors can cause severe bias in estimates of effects of interest (Boe et al., 2020; Giganti et al., 2020; Oh et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Using a validation data where both the true and error-prone survival times are both available, Braun et al (2018) proposed a nonparametric bias correction procedure for models using 𝒯 𝒯 𝒯 as predictors. Gravel et al (2018) proposed the model-based estimation accounting for temporally induced errors and misclassified event errors in time-to-event outcomes. Recently, Oh et al (2021) developed a raking and regression calibration method for data with measurement errors in both covariates and time-to-event outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Gravel et al. (2018) proposed the model‐based estimation accounting for temporally induced errors and misclassified event errors in time‐to‐event outcomes. Recently, Oh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Covariate measurement error, particularly classical measurement error or extensions of it, has been well studied in the literature and methods to correct the bias resulting from such error have been well developed (Carroll et al, 2006). Although less attention has been given to errors in an outcome of interest, there has been some recent work looking at errors in binary outcomes (Magder and Hughes, 1997;Edwards et al, 2013;Wang et al, 2016), discrete time-to-event outcomes (Meier et al, 2003;Magaret, 2008;Hunsberger et al, 2010), and to a lesser extent, continuous time-to-event outcomes (Oh et al, 2018;Gravel et al, 2018). There has been even less work to understand the impact of errors in both covariates and a time-to-event outcome, but it has recently been shown that ignoring such errors can cause severe bias in estimates of effects of interest (Oh et al, 2019;Boe et al, 2020;Giganti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%